Black widow [compact disc, unabridged] - White, Randy Wayne (White, Randy Wayne. Doc Ford series., 2008)
Doc Ford's goddaughter pleads with him to help her out of a jam. An extortionist with a lurid videotape of her bachelorette party is threatening to ruin her imminent marriage. Despite getting paid, the blackmailer releases the tape anyway--and that's only the beginning of Doc's troubles.